IMPLEMENTASI MONITORING PEMBAYARAN PADA METODE AGILE BERBASIS WEB STUDI KASUS SD MUHAMMADIYAH 03 KREATIF - Rita Yulianti; Firmansyah; Eko Bakkara Fransisko; Roeslan Djutalov (Journal of Research and Publication Innovation, 2023)
Based on research and testing conducted, it can be concluded that 90.25% of respondents stated that this application is worth using to help users process payment data in schools. This shows that the majority of respondents find this system useful and can meet their needs. However, 9.75% of respondents stated that this application still needs to be redeveloped.This indicates that there are still some shortcomings or features that need to be fixed or added to this online payment system. Feedback from respondents who consider it necessary to redevelop can be the basis for making improvements and improvements to the system. The use of payment systems at SD Muhmmadiyah 03 Kreatif School can provide benefits in managing payment data. However, it is important to continue to evaluate, develop, and improve so that this system can continue to meet user needs and make an optimal contribution in the world of education.